Optimasi Proses Pembuatan Laporan Keuangan dengan Software Akuntansi Manager.io pada Cafe Abang - Candy Candy; Michelle Selvia Liu (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Manual financial management often hinders the efficiency and accuracy of financial reporting in micro, small, and medium enterprises (MSMEs). Cafe Abang, an MSME in Batam, faces challenges in maintaining effective financial records, which leads to delays and inaccuracies in its financial reports. The purpose of this community service project is to implement Manager.io accounting software as a digital solution for the financial system, enabling the management team to generate accurate and timely basic financial reports. The methods used in this activity include observation, interviews, and training on the software for the owner and manager of Cafe Abang. The results of the service showed that after the implementation of Manager.io, the owner and managers were able to generate income statements, balance sheets, and cash flow reports automatically and accurately, reducing recording errors and enhancing financial transparency.